ANALYSIS OF ENVIRONMENTAL AND SANITARY KNOWLEDGE OF SHELLFISH GATHERERS IN VERGEL DO LAGO, MACEIÓ/AL-BRAZIL, BEFORE AND AFTER EDUCATIVE ACTION - do Nascimento, Cynthia Wanessa Souza; Araujo, Daniel de Magalhães (Caminhos de Geografia, 2022)
Fishing and processing of sururu in Mundaú lagoon (Maceió-AL) are carried out in a precarious sanitary situation. In addition, their shells are improperly discarded, aggravating environmental problems. This study was carried out with the aim of analyzing the knowledge of shellfish gatherers about environmental issues before and after an educational action. Therefore, a social characterization of them was carried out, as well as an analysis of their previous knowledge about environmental issues and good practices in food processing, by interviews based on semi-structured questionnaires, made before and after the educational action. Almost all shellfish gatherers (96.43%) were women, with 60.71% having only incomplete primary education and a maximum monthly income of RS400.00 for 82.15%. All respondents understand that pollution affects their community, 71.43% of them considering the Mundaú lagoon polluted, 67.86% pointing out that pollution affects sururu fishing, and 71.43% recognizing that it affect negatively the quality of the sururu meat. Regarding good food handling practices, it was found that although there is an understanding of them, not everyone adopts them. Data from the post-educational action show that the promotion of educational practices contributes to improving the sururu production model and environmental knowledge, mitigating the impacts of shell disposal.